Virtual Reality Therapy for Reducing Anxiety in Patients with Drug-Resistant Tuberculosis - Abdillah, Awaludin Jahid; Ayu, Windri Dewi; Rianzares, Glenn L. (International Journal of Nursing Information, 2025)
Drug-resistant tuberculosis (DR-TB) presents both a biological challenge and a substantial psychological burden, particularly anxiety, which often disrupts treatment adherence and diminishes patients' quality of life. This study aimed to evaluate the effectiveness of Virtual Reality (VR) therapy as a non-pharmacological intervention for reducing anxiety levels among DR-TB patients. A quasi-experimental design with a pretest-posttest control group approach was employed. A total of 384 participants were recruited from Indonesia and Philippines. Anxiety levels were assessed using the validated Hamilton Anxiety Rating Scale. Data were analyzed using paired t-tests to assess within-group changes, and Analysis of Covariance (ANCOVA) was conducted to control for potential confounding variables and determine between-group differences. The results revealed a statistically significant reduction in anxiety scores in the VR group compared to the control group (p < 0.001), with participants reporting improved emotional regulation and reduced psychological distress. These findings suggested that VR therapy was an effective non-pharmacological strategy for managing anxiety in DR-TB patients. The study contributed to the digital mental health literature by offering culturally relevant evidence on the application of immersive therapy in two high-burden TB countries. Integrating VR therapy into TB care protocols may enhance holistic patient management, particularly in resource-constrained healthcare systems.